Напрями вдосконалення управлінського консультування підприємств в умовах фінансової кризи - Черепанова, Вікторія Олександрівна; Солодовнікова, Тетяна Володимирівна; Пивовар, В. М. (НТУ "ХПІ", 2014)
Пропонуються способи розширення бізнесу з управлінського консультування шляхом використання міжнародного маркетингу та фінансового менеджменту. Зроблено висновки про необхідність розширення географії бізнесу та підвищення його результативності.

We offer ways to expand the business of management consulting through the use of international marketing and financial management. The conclusions about the need for geographical expansion of business and increase its effectiveness. This paper proposes the use of a matrix organizational structure of the project approach in the implementation of consulting firms in Western markets krayin. Z this purpose invited to the restructuring of the marketing department activity in international marketing. In addition, the paper presents how to evaluate personnel for its quality, and performance. These measures are aimed at improving the performance of the firm of management consulting and market expansion of these services.
Areas of improvement of management consulting companies in the financial crisis
Keywords: ринок консультаційних послуг; міжнародний маркетинг; фінансові інвестиції; фінансовий менеджмент; консалтингові фірми; management consulting; international marketing; financial investment; financial managemen; consulting